Association of Circulating Cell-Free Mitochondrial DNA With Sudden Sensorineural Hearing Loss - Yang, Chao-Hui; Yang, Ming-Yu; Lin, Wei-Che; Hwang, Chung-Feng; Lin, Yu-Tsai; Wu, Ching-Nung; Chen, I-Ya; Tsai, Ming-Hsien (Otolaryngology-head and neck surgery, 2025)
To evaluate the association of circulating cell-free mitochondrial DNA (ccf-mtDNA) levels with the severity and treatment outcomes of sudden sensorineural hearing loss (SSNHL). Observational prospective study. Tertiary academic medical center. Plasma samples were collected from patients diagnosed with SSNHL in the morning before steroid treatment, as well as from healthy controls. A quantitative polymerase chain reaction was used to measure ccf-mtDNA levels, expressed as log copy numbers per milliliter. Treatment outcomes were evaluated using hearing gain, percentage of recovery, and Siegel's criteria. The study included 80 subjects, including 50 patients and 30 healthy controls. The mean (SD) plasma ccf-mtDNA level was 8.1 (0.35), which was significantly higher than 7.78 (0.65) controls (95% CI: 0.097-0.542). Patients with good recovery exhibited significantly higher pretreatment ccf-mtDNA levels compared to those with poor recovery (mean [SD] score: 8.29 [0.34] vs 8.02 [0.33]; 95% CI: 0.04-0.48). Ccf-mtDNA levels were positively associated with hearing gain (r = 0.486, 95% CI: 0.227-0.663) and percentage of recovery (r = 0.361, 95% CI: 0.103-0.574). Multivariate analyses revealed that less than 7 days from onset of hearing loss to treatment (odds ratio [OR]: 7.389, 95% CI: 1.324-41.239) and higher ccf-mtDNA levels (OR: 24.634, 95% CI: 1.878-323.163) were independent predictors for good recovery. Plasma ccf-mtDNA levels were elevated in patients with SSNHL and were significantly associated with better treatment outcomes following steroid therapy. These findings suggest that ccf-mtDNA levels may serve as a predictive biomarker for SSNHL treatment outcomes, paving the way for personalized therapeutic strategies.